Las prácticas políticas en la comunidad digital de Facebook: @Deslengua2 - Avellaneda Prieto, Ana Sofía (2020)
This research is relevant since it seeks to analyze and highlight the importance of digital media for information spaces and political debate. The results of the findings will also contribute to determining the effectiveness and efficiency of social networks based on this theme, which will be a great contribution as it is a recent research topic. Within the social sphere, it is expected to describe how individuals (users and prominent fans of @ Deslengua2) are the main actors of the page, since, without their interactions, the publications of the page would not have the great impact that they have thanks to to them.